NK cell based immunotherapy against oral squamous cell carcinoma - Zhang, Ying; Xie, Jianming; Wu, Haoran; Huang, Jinhui; Zheng, Danna; Wang, Shaotong; Jia, Xueqiang; He, Zongzhong; Gong, Ying; Ju, Linling; Sun, Qiurong (Frontiers in Immunology, 2024)
Oral squamous cell carcinoma (OSCC), a major subtype of head and neck cancers, presents significant challenges due to its aggressive feature and limited therapeutic efficacy of conventional treatments. In response to these challenges, Natural Killer (NK) cells, a vital component of the innate immune system, are being explored for their therapeutic potential in OSCC due to their inherent ability to target and eliminate cancer cells without prior sensitization. This review uniquely focuses on the evolving role of NK cells specifically in OSCC, incorporating recent advancements in CAR-NK cell engineering and personalized therapy approaches that have not been comprehensively covered in previous reviews. The mechanisms through which NK cells exert cytotoxic effects on tumor cells include direct killing through the engagement of natural cytotoxic receptors and antibody-dependent cellular cytotoxicity (ADCC), making them promising agents in cancer immunotherapy. Additionally, the article explores recent advancements in engineering NK cells to enhance their antitumor activity, such as the modification with chimeric antigen receptors (CARs) to target specific tumor antigens. Clinical implications of NK cell-based therapies, including the challenges of integrating these treatments with existing protocols and the potential for personalized therapy, are examined. The review highlights the promise of NK cell therapies in improving outcomes for OSCC patients and outlines future directions for research in this dynamic field of oncological immunotherapy.